Hardiness in the profession of sports coaches and physical education teachers - Korobeinikova, I.; Korobeynikov, G.; Kokun, O.; Raab, M.; Korobeinikova, L.; Syvash, I. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. To study psychological features of sports coaches and physical education teachers` professional hardiness.